Udje Družbe sv. Mohorja v ZDA od leta 1901 do leta 1916 - Vovko, Andrej (Traditiones (Ljubljana), 1997)
Through the 140 years of its history, the St. Hermagoras Society has performed an important religious, nationally revivalist, cultural and educational mission among the Slovenes both at home and among immigrants. In addition to two "inspections" of the U.S. territory, the article gives a yearly survey of teh Society members and the network of centers of the St. Hermagoras Society in the U.S.A. from 1901 to 1916, complete with charts on the top 35, including data on the number of members, subscribers and representatives.
Keywords: Družba sv. Mohorja; Hermagoras Society; slovenski izseljenci; United States of America; ZDA; založbe; Slovenci; Slovenes; 1901/1916